Analysis of China's Telecommunication Business Strategies Based on Porter's Five-Force Model on 4G Era - Yonghui Zhang; Wanli Hu (Dianxin kexue)
The analysis of the current operating environment and market competition of China's telecommunications industry were illustrated based on Porter's Five-Force model. On the 4G era, it will be emerged a new pattern of“3+N+N”of China's telecommunications market in future. Based on this market structure, in the 4G market, China's telecom market participants should adopt different business strategies according to their own conditions, such as differentiation, cost leadership and industry-specific focus, etc.